Multi factor equity model for shariah investment / Shahril Simon - Shahril , Simon (2015)
The study is set out to discover a new multi factor model for Shariah investing in Malaysian stocks based on musharakah principle. It also wants to know the model explanatory power of stocks‟ risk decomposition and return attribution as well to forecast risk given the current volatile market. Existing single factor model such as Capital Asset Pricing Model and multi factor model like Fama French Model are formulated on the basis of risk-free rate element in which rescind out with Shariah principle of musharakah. Moreover, the models do not explained their factors well in emerging markets that include Malaysia. Thus, exploring the alternative model is pertinent. A fundamental factor model is carefully constructed from four key essential elements of musharakah: Business Sector, Management Quality, Profitability Growth and Capital Strength factors. It gives greater insight into the sources of stocks performance and leads to intuitive action items. The cross-sectional approach is used to build the model. Key results show that the model has high explanatory power for contemporaneous returns, maintains high forecasting ability in high and low volatility environments and stays unbiased with no significant under-forecasting or over-forecasting of risk for a broad variety of portfolios. Despite the existence of long established multi factor models, this study offers new empirical evidence suggesting the application of musharakah principle as a framework, although without risk-free rate element, is able to increase the explanatory power of Shariah-compliant stocks‟ risk and return. Moreover, it goes well with those who subscribe to principle based investing.